Strategi Gereja Dalam Menumbuhkan Iman Jemaat di Jemaat GMIM Getsemani Maumbi - Madsen Pusung (ATOHEMA: Jurnal Teologi Pastoral Konseling, 2026)
This introduction begins with the congregation assembly at the church in service which is expected to be an effortto develop the growth of faith of congregation members at the Evangelical Christian Church in Minahasa (GMIM)Gethsemane Maumbi Congregation, Eris District, Minahasa Regency, North Sulawesi. The aim of this research isto determine the assistance strategy for the congregation in strengthening the faith of the congregation. Thisresearch uses qualitative research with a case study approach as the research methodology. Interviews are usedfor data collection, and reduction, display, and verification are used for data analysis. The consequences of thisexamination show that faith growth is a successful strategy for developing congregational trust and faith growth.Conversations with the pastor, with the congregation, and assistance during difficult times are examples ofpastoral care. The growth of the congregation's faith should be seen from the members of the congregation whowere initially neither dynamic nor harmonious in worship, becoming determined to provide praise and worship inwitnessing, fellowshipping and serving the church for God.